1989
DOI: 10.1007/bf01658393
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic laser therapy in the curative and palliative treatment of upper gastrointestinal cancer

Abstract: Endoscopic laser treatment was initially applied for gastrointestinal bleeding, but has been actively extended, especially in Japan, to the curative treatment of early upper gastrointestinal cancers. We have treated 10 cases of early gastric cancer and 1 case of early esophageal cancer by Nd-YAG laser radiation, and 2 cases of early gastric cancer by photochemical therapy (PCT) with argon laser + hematoporphyrin derivative. Also, 62 cases of advanced cancer were treated, 10 of the esophagus and 52 of the stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 6 publications
2
31
0
Order By: Relevance
“…Although surgical palliation is an available option in such patients, the results of palliative gastric bypass surgery are poor with high rates of morbidity and mortality [6][7][8] . Because of the limitations of surgery and because many patients are elderly, frail, and in an advanced stage of disease, various techniques for restoration of bowel function by non-surgical means (eg, balloon dilation and laser photoablation) have been proposed; all have met with limited success [9,10] . Since the endoscopic application of SEMS to malignant gastric outlet obstruction in the early 1990s, the use of SEMS to pass through an obstructing neoplasm with minimal morbidity has become increasingly widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical palliation is an available option in such patients, the results of palliative gastric bypass surgery are poor with high rates of morbidity and mortality [6][7][8] . Because of the limitations of surgery and because many patients are elderly, frail, and in an advanced stage of disease, various techniques for restoration of bowel function by non-surgical means (eg, balloon dilation and laser photoablation) have been proposed; all have met with limited success [9,10] . Since the endoscopic application of SEMS to malignant gastric outlet obstruction in the early 1990s, the use of SEMS to pass through an obstructing neoplasm with minimal morbidity has become increasingly widespread.…”
Section: Discussionmentioning
confidence: 99%
“…More nodal involvement occurred in tumors larger than 1.0 cm in superficial diameter (21%), then in those with depressed macroscopic type (IIc or III; 23%) and in those with ulcer formation (36%), but no Macroscopic type, according to reference [13] b Histological type, according to reference [13] cally, the incidence of lymph node metastasis in mucosal gastric cancer has been reported as 1.3% to 5.0% [11,12,[15][16][17]. Recently, it has been reported that mcancer with a tumor smaller than 2 cm in diameter, of the well differentiated type or the elevated macroscopic type, has no lymph node metastasis.…”
Section: Association With Clinicopathological Characteristicsmentioning
confidence: 99%
“…Recent investigations have reported that micrometastases to lymph nodes that were overlooked by ordinary hematoxylin and eosin (H&E) staining could be detected by cytokeratin (CK) immunostaining, and these so-called micrometastases were found to have prognostic significance [7][8][9][10]. Mucosal gastric cancer (m-cancer) has been the prime candidate for less invasive surgery or endoscopic mucosal resection (EMR) [11,12]. However, the frequency or outcome of occult involvement in lymph nodes from m-cancer remains unclear.…”
mentioning
confidence: 99%
“…[8]. The Nd: YAG laser and PDT are also effective options for managing bleeding from an unresectable esophageal tumor [9,10].…”
Section: Unresectable Esophageal Cancermentioning
confidence: 99%